Transgressing Disciplinary Bounds: Historiographical Directions in South Africa's History/Heritage Affinities - Manyane, Ralph (African historical review, 2023)
A stronger history/heritage relationship with a much longer genealogy than has hitherto been examined is explored in this article. Deploying a cultural-historical method alongside the Tswaing and Mphebatho museums, this study attempts to open more and new space for exploring the making of South Africa's history- and heritage-making. Investing both transdisciplinary fields with potentially transformative and truly decolonising qualities entrusts them with social roles necessary for indigenous society's survival. Not only do the deployed methodologies allow an in-depth historical investigation of heritage sites, but they also warrant transcendence beyond entrenched binaries between history and heritage and colonial-sponsored temporal frames. In this way, the text explores long-held and previously little-treated indigenous concepts of history and heritage which evolved into the colonial and post-colonial eras. As locations whose heritage profiles embrace human and non-human worlds, the selected museums illustrate how a broadened eco-culture heritage interfaces with history and identity. The two museums therefore encapsulate memory, indigenous knowledge, and culture generated over time through complex or intricate linkages with landscape and nature.